Pesantren : dari transformasi metodologi menuju demokratisasi institusi - Qomar, Mujamil, 1965- (Ciracas, Jakarta : Erlangga, 2005)
On the curriculum and educational system of Islamic religious training centers in Indonesia.
Revision of the author's thesis (S2)--IAIN Sunan Ampel, 1996
Includes bibliographical references (p. [197]-204)
Bibliografi : p. [197]-204
Keywords: Islam and politics -- Indonesia; Islamic education -- Indonesia